Spatial speech-in-noise performance in simulated single-sided deaf and bimodal cochlear implant users in comparison with real patients. (3rd January 2023) - Jürgens, Tim; Wesarg, Thomas; Oetting, Dirk; Jung, Lorenz; Williges, Ben
Abstract: Objective: Speech reception thresholds (SRTs) in spatial scenarios were measured in simulated cochlear implant (CI) listeners with either contralateral normal hearing, or aided hearing impairment (bimodal), and compared to SRTs of real patients, who were measured using the exact same paradigm, to assess goodness of simulation. Design: CI listening was simulated using a vocoder incorporating actual CI signal processing and physiologic details of electric stimulation on one side. Unprocessed signals or simulation of aided moderate or profound hearing impairment was used contralaterally. Three spatial speech-in-noise scenarios were tested using virtual acoustics to assess spatial release from masking (SRM) and combined benefit. Study sample: Eleven normal-hearing listeners participated in the experiment. Results: For contralateral normal and aided moderately impaired hearing, bilaterally assessed SRTs were not statistically different from unilateral SRTs of the better ear, indicating "better-ear-listening". Combined benefit was only found for contralateral profound impaired hearing. As in patients, SRM was highest for contralateral normal hearing and decreased systematically with more severe simulated impairment. Comparison to actual patients showed good reproduction of SRTs, SRM, and better-ear-listening. Conclusions: The simulations reproduced better-ear-listening as in patients and suggest that combined benefit in spatial scenes predominantly occurs when both ears show poor speech-in-noise performance.